Ray Casting for Iso-surface in Volumetric Data - Ngoc Anh, Do Hoang (universiti teknologi petronas, 2005)
Volume data visualization is an active field of research and development. It can be applied in many areas such as medical, oil and gas exploration, etc... Although volume visualization is highly computational cost, there is a vision of real time volumetric visualization systems based on interactive ray tracing. Over the years, many rendering algorithms have been created and enhanced. The focus of this project is to develop a simple ray casting program for volumetric data. The program will be able to render specific volume data using a single processor in a reasonable amount of time. It is opento improve for implementation on multiprocessors. The thesis will compare some existing algorithms for ray casting in terms of image quality, computing time, complexity and so forth. The thesis includes a proposal of new multisampling algorithm, which significantly reduces rendering time while producing similar quality of image with existing algorithms.